Authenticity, rapport and interactional justice in frontline service: the moderating role of need for uniqueness. Issue 3 (9th November 2020) - Lindsey-Hall, Kristina K.; Jaramillo, Susana; Baker, Thomas L.; Arnold, Julian M.
Abstract : Purpose: This paper aims to investigate how perceptions of employee authenticity and customer–employee rapport influence customers' interactional justice assessments and related service evaluations, and how customers' need for uniqueness impacts these relationships. Design/methodology/approach: A multi-method, three-study design is used to test the research model. Specifically, structural equation modeling provides tests of the main hypotheses, and two supplemental experimental studies tease out conditional effects providing insightful managerial contributions. Findings: Results indicate that customers' perceptions of employee authenticity affect customers' interactional justice evaluations, particularly when customers identify high levels of customer–employee rapport. Additionally, the aforementioned relationships are contingent upon customers' need for uniqueness, such that customers with higher levels of need for uniqueness experience lower levels of customer–employee rapport and, consequently, provide poorer interactional justice assessments. Finally, conditional effects are found given the type of provider and frequency of visit. Originality/value: This research extends prior efforts to understand how customer–employee dynamics influence customers' service encounter evaluations. In particular, it furthers understanding of authentic FLE–customer encounters, explores drivers of interactional justice and explicates how consumers' varying levels of need for uniqueness have differential effects on service outcomes.